2002
DOI: 10.1292/jvms.64.245
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Species Distribution of Staphylococci from Animal and Human Skin.

Abstract: ABSTRACT. From April 1999 to December 2000, a survey was made on the distribution of Staphylococcus species on the skin of 7 kinds of animals and humans. Staphylococci were isolated from 12 (100%) of 12 pigs, 17 (89.5%) of 19 horses, 30 (100%) of 30 cows, 73 (90.1%) of 81 chickens, 10 (40%) of 25 dogs, 23 (76.7%) of 30 laboratory mice, 20 (52.6%) of 38 pigeons, and 80 (88.9%) of 90 human beings. The predominant staphylococci isolated from a variety of animal species were novobiocin-resistant species, S. xylosu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
133
3
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(147 citation statements)
references
References 24 publications
6
133
3
5
Order By: Relevance
“…In this respect, a report also suggested that the possible source of S. sciuri colonization in surgical wounds may be flies perching on open wounds (Kolawole and Shittu, 1997).Thus, it is assumed that frequent contact with healthy domestic and farm animals may also contribute to an at least temporary colonization of the skin, and subsequently the wounds, by S. sciuri (Kloos et al, 1976;Nemeghaire et al, 2014b). Despite the rare occurrence of S. sciuri in humans (Marsou et al, 1999;Couto et al, 2000;Nagase et al, 2002), some reports furthermore point to the role of S. sciuri as opportunistic pathogens isolated from various clinical specimen and causing serious infections in humans such as endocarditis, peritonitis, septic shock, and wound infections (Hedin and Widerstrom, 1998;Wallet et al, 2000;Horii et al, 2001;Stepanovic et al, 2002Stepanovic et al, , 2003). Moreover, despite the lack of data regarding S. sciuri colonization of the handler, a recurrent transmission from the handler to the horse http: //www.openveterinaryjournal.com H. Beims et al Open Veterinary Journal, (2016), Vol.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, a report also suggested that the possible source of S. sciuri colonization in surgical wounds may be flies perching on open wounds (Kolawole and Shittu, 1997).Thus, it is assumed that frequent contact with healthy domestic and farm animals may also contribute to an at least temporary colonization of the skin, and subsequently the wounds, by S. sciuri (Kloos et al, 1976;Nemeghaire et al, 2014b). Despite the rare occurrence of S. sciuri in humans (Marsou et al, 1999;Couto et al, 2000;Nagase et al, 2002), some reports furthermore point to the role of S. sciuri as opportunistic pathogens isolated from various clinical specimen and causing serious infections in humans such as endocarditis, peritonitis, septic shock, and wound infections (Hedin and Widerstrom, 1998;Wallet et al, 2000;Horii et al, 2001;Stepanovic et al, 2002Stepanovic et al, , 2003). Moreover, despite the lack of data regarding S. sciuri colonization of the handler, a recurrent transmission from the handler to the horse http: //www.openveterinaryjournal.com H. Beims et al Open Veterinary Journal, (2016), Vol.…”
Section: Introductionmentioning
confidence: 99%
“…Staphylococcus aureus is widespread in nature and commonly found on human skin, skin glands and mucous membranes (Nagase et al, 2002). The skin microbiota plays a very important role in preventing many pathogens from colonizing the skin and causing disease, in a similar manner to the 'barrier effect' produced by intestinal microbes.…”
mentioning
confidence: 99%
“…sciuri, and S. aureus was 69.6%, 43.5%, and 39.1%, respectively (Nagase et al, 2002). Obviously, although S. sciuri was normally isolated from both oral (Trudel et al, 1986;Nakano, 1989;Hauschild and Schwarz, 2003) and normal skin (Nagase et al, 2002) from laboratory mice, the present case demonstrated its individually opportunistic pathogen property.…”
Section: CMmentioning
confidence: 50%
“…Obviously, although S. sciuri was normally isolated from both oral (Trudel et al, 1986;Nakano, 1989;Hauschild and Schwarz, 2003) and normal skin (Nagase et al, 2002) from laboratory mice, the present case demonstrated its individually opportunistic pathogen property. However, the disease natural history of S. sciuri, claiming it as an opportunistic pathogen is still controversial with a wide spectrum of predisposed factors including host, strain, and environmental factors (Hedin and Widerstrom, 1998).…”
Section: CMmentioning
confidence: 53%